Phosphate-enhanced stationary-phase fitness of Escherichia coli is related to inorganic polyphosphate level - Schurig Briccio, Lici Ariane (2009)
We found that Escherichia coli grown in media with >37 mM phosphate maintained a high polyphosphate level in late stationary phase, which could account for changes in gene expression and enzyme activities that enhance stationary-phase fitness. Copyright © 2009, American Society for Microbiology. All Rights Reserved.